2016
DOI: 10.1038/srep36045
|View full text |Cite
|
Sign up to set email alerts
|

HULC cooperates with MALAT1 to aggravate liver cancer stem cells growth through telomere repeat-binding factor 2

Abstract: The dysregulation of lncRNAs has increasingly been linked to many human diseases, especially in cancers. Our results demonstrate HULC, MALAT1 and TRF2 are highly expressed in human hepatocellular carcinoma tissues, and HULC plus MALAT1 overexpression drastically promotes the growth of liver cancer stem cells. Mechanistically, both HULC and MALAT1 overexpression enhanced RNA polII, P300, CREPT to load on the promoter region of telomere repeat-binding factor 2(TRF2), triggering the overexpression, phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…Looking into the subnetwork associated with G1‐S phase transition, we identified 2 important lncRNAs (MALAT1 and DANCR), which are previously reported to be involved in the regulation of stem cell properties . These 2 lncRNAs are investigated further to hypothesize their probable role as RNA decoys in G1‐S phase transition of hESCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking into the subnetwork associated with G1‐S phase transition, we identified 2 important lncRNAs (MALAT1 and DANCR), which are previously reported to be involved in the regulation of stem cell properties . These 2 lncRNAs are investigated further to hypothesize their probable role as RNA decoys in G1‐S phase transition of hESCs.…”
Section: Resultsmentioning
confidence: 99%
“…Looking into the subnetwork associated with G1-S phase transition, we identified 2 important lncRNAs (MALAT1 and DANCR), which are previously reported to be involved in the regulation of stem cell properties. [42][43][44][45][46] These 2 lncRNAs are investigated further to hypothesize their probable role as RNA decoys in G1-S phase transition of hESCs. However, our study could not predict lncPRESS1, a lncRNA which is already known to act as an RNA decoy by interacting with SIRT6 and induce the expressions of pluripotent genes in hESCs to maintain pluripotency 27 as well as few other lncRNAs associated with pluripotency.…”
Section: Functional Annotation Of Lncrna-tfm-gene Subnetwork Involvmentioning
confidence: 99%
“…Chromatin immunoprecipitation was carried out according to methodology as previously described 26. Briefly, cells were cross‐linked with 1% (v/v) formaldehyde (Sigma‐Aldrich) for 10 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…202,203 A recent report showed that long ncRNAs are highly expressed in HCC, and they promote liver cancer stem cell growth through epigenetic regulation. 204 Cheng et al study showed that liver-specific miR-122 is epigenetically suppressed by HOTAIR, leading to activation of Cyclin G1 and HCC growth. 205 Recent research from our laboratory shows that hepatic adaptive response to HCV-induced ER stress and oxidative stress can silence miR-122 through induction of the STAT3-HNF4α-miR-24 inflammatory feedback loop.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%